2011
DOI: 10.1152/ajpendo.00225.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal dietary n-3 and n-6 fatty acids on milk medium-chain fatty acids and the implications for neonatal liver metabolism

Abstract: Levels of n-6, n-3, and medium-chain fatty acids (MCFA) in milk are highly variable. Higher carbohydrate intakes are associated with increased mammary gland MCFA synthesis, but the role of unsaturated fatty acids for milk MCFA secretion is unclear. This study addressed whether n-6 and n-3 fatty acids, which are known to inhibit hepatic fatty acid synthesis, influence MCFA in rat and human milk and the implications of varying MCFA, n-6, and n-3 fatty acids in rat milk for metabolic regulation in the neonatal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
0
21
0
2
Order By: Relevance
“…In humans impaired MCFA oxidation is associated with neonatal metabolic disorders and elevated morbidity [46], and animal model studies have demonstrated that MCFA are more readily absorbed by the gut and transported to the liver for oxidation than long chain fatty acids (LCFA) [47], [48]. These observations indicate that MCFA may be the preferred energy source for growth in the developing neonate, and suggest that reduced MCFA consumption would alter neonatal metabolic properties and lead to impaired growth.…”
Section: Discussionmentioning
confidence: 99%
“…In humans impaired MCFA oxidation is associated with neonatal metabolic disorders and elevated morbidity [46], and animal model studies have demonstrated that MCFA are more readily absorbed by the gut and transported to the liver for oxidation than long chain fatty acids (LCFA) [47], [48]. These observations indicate that MCFA may be the preferred energy source for growth in the developing neonate, and suggest that reduced MCFA consumption would alter neonatal metabolic properties and lead to impaired growth.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid composition of total lipids of breast muscle and feed was determined by gas chromatography [29]. Fatty acid content is presented as g fatty acid/kg tissue (wet weight), and as weight percentage of the measured fatty acids.…”
Section: Methodsmentioning
confidence: 99%
“…TAGs containing SCFAs, MCFAs and to some extent also lauric acid, with 12 carbon atoms, are more rapidly hydrolysed by gastrointestinal lipases and the hydrolysis products are more easily absorbed and are taken to the liver directly via the portal vein (Novak and Innis, 2011). The ingestion of these fatty acids, therefore, could provide some benefit under conditions where fat absorption is a limiting factor.…”
Section: Fat Composition Of Human Milkmentioning
confidence: 99%
“…The ingestion of these fatty acids, therefore, could provide some benefit under conditions where fat absorption is a limiting factor. The MCFA content of human milk varies and is increased by a high carbohydrate and low fat intake of the mother (Koletzko et al, 1992;Sauerwald et al, 2001;Novak and Innis, 2011).…”
Section: Fat Composition Of Human Milkmentioning
confidence: 99%